Acoustic environments matter: Synergistic benefits to humans and ecological communities. (1st December 2017) - Francis, Clinton D.; Newman, Peter; Taff, B. Derrick; White, Crow; Monz, Christopher A.; Levenhagen, Mitchell; Petrelli, Alissa R.; Abbott, Lauren C.; Newton, Jennifer; Burson, Shan; Cooper, Caren B.; Fristrup, Kurt M.; et al.
Abstract: Protected areas are critical locations worldwide for biodiversity preservation and offer important opportunities for increasingly urbanized humans to experience nature. However, biodiversity preservation and visitor access are often at odds and creative solutions are needed to safeguard protected area natural resources in the face of high visitor use. Managing human impacts to natural soundscapes could serve as a powerful tool for resolving these conflicting objectives. Here, we review emerging research that demonstrates that the acoustic environment is critical to wildlife and that sounds shape the quality of nature-based experiences for humans. Human-made noise is known to affect animal behavior, distributions and reproductive success, and the organization of ecological communities. Additionally, new research suggests that interactions with nature, including natural sounds, confer benefits to human welfare termed psychological ecosystem services. In areas influenced by noise, elevated human-made noise not only limits the variety and abundance of organisms accessible to outdoor recreationists, but also impairs their capacity to perceive the wildlife that remains. Thus soundscape changes can degrade, and potentially limit the benefits derived from experiences with nature via indirect and direct mechanisms. We discuss the effects of noise on wildlife and visitors through the concept of listening area and demonstrate how the perceptual worlds of both birds and humans are reduced by noise. Finally, we discuss how management of soundscapes in protected areas may be an innovative solution to safeguarding both and recommend several key questions and research directions to stimulate new research. Graphical abstract: Highlights: Protected areas are key for biodiversity preservation & human experiences in nature. Sounds of nature confer psychological ecosystem services to people. Anthropogenic noise degrades the acoustic environment in many protected areas. Degraded acoustics reduce biodiversity & limit human experiences in nature. Protected area noise management could safeguard biodiversity and human experiences.